Research on tropical pathology in the department of Madre de Dios - Cornejo Donayre, Alberto (1958)
During the month of Augusto 1957, we realized epidemiological investigations about Chagas disease in the department of Madre de Dios which can be summarized by the following conclusions : 1.- In the principal populated centers of the department of Madre de Dios there are epidemiological conditions which favor the dissemination of Trypanosomiasis cruzi. The human dwelling is overpopulated, its in habitants live in promiscuity with the domestic animal, which in other places of America they play the role or reservoirs of T. cruzi and the characteristics of the construction permits entrance, permanence and, reproduction of triatominos. 2.- In Puerto Maldonado city Rhodnius pallescens has been found, showing that hapyly it has not adapted itself to the characteristicas of the dwelling in that area, to which it enters circunstantially. 3.- It has been, proved that in Madre de Dios R. pallescens is naturally infected by T. cruzi and probably some wild mammals are also naturaly infected and act as reservoirs to this trypanosomiasis. 4.- The examination of 904 smears and thick drops of perriferal blood of equal number of residents in Madre de Dios, has been negative for T. cruzi. In this group, 591 persons were sumbimitted to the clinical examination and failed to show any symptoms or signals of Chagas disease. 5.- Seventy-four xenodiagnostics made in equal number of persons, from the group studied in Madre de Dios, grave negative results. 6.- Chagas disease is not a public health problem in that department but the conditions of the dwellings, the existense of the etiological agent; of vector and a wild animal which act as reservoir, obliges that extreme profilatic measures be taken to avoid disemination of the disesase.